2015
DOI: 10.1111/ped.12749
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric granulomatous orchitis: Case report and review of the literature

Abstract: An 11-year-old boy presented with fever and abdominal pain, and was diagnosed with retroperitoneal lymphadenitis. At the same time, a painless right scrotal mass was observed. On imaging the testis and the epididymal mass both had abundant blood flow, although tumor markers were negative. Although the right testis had shrunk after antibiotic treatment, swelling was persistent and incisional biopsy was therefore performed, resulting in diagnosis of granulomatous orchitis (GO). No recurrence was found. In cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…It was first reported by Grunberg in 1926, and is described as a non-specific inflammation of the testicles, seen in middle-aged and elderly men, with unknown etiology. 1 3 It is generally thought to be related to testicular trauma, urinary tract infection, or autoimmunity. 2 , 4 7 The clinical symptoms are atypical, usually involving one testicle; the onset may be rapid or slow, affected testicles are enlarged and hard, and these findings may be accompanied by pain and swelling.…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported by Grunberg in 1926, and is described as a non-specific inflammation of the testicles, seen in middle-aged and elderly men, with unknown etiology. 1 3 It is generally thought to be related to testicular trauma, urinary tract infection, or autoimmunity. 2 , 4 7 The clinical symptoms are atypical, usually involving one testicle; the onset may be rapid or slow, affected testicles are enlarged and hard, and these findings may be accompanied by pain and swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that B-ultrasound-guided fine needle biopsy (FNA) has diagnostic significance for yellow granulomatous pyelonephritis and cholecystitis, and FNA is expected to become a useful tool for preoperative diagnosis of XGO [16], which may prevent orchiectomy due to unexpected diagnosis.The general management of xanthogranulomatous orchitis includes anti-inflammatory, analgesic, detumescent, and symptomatic treatment, but the effect is not ideal. Orchiectomy for [17] was ultimately chosen in many cases. In adolescents with testicular swelling and pain, anti-infective treatment is generally preferred.…”
Section: C B Amentioning
confidence: 99%
“…Xantho-granulomatous orchitis (XGO) is a rare, nonmalignant lesion diagnosed while evaluating testicular mass. [1][2][3] Many at time, it becomes difficult to diagnose this rare entity based on clinical & radiological findings. A detailed histological evaluation is necessary to rule out any malignancy and give a definitive diagnosis of XGO.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed histological evaluation is necessary to rule out any malignancy and give a definitive diagnosis of XGO. 2,3 Very few cases of XGO have been reported in the literature till date. [2][3][4][5][6][7] Here in we describe this rare entity in a 45-yearold male, who presented to hospital with right testicular swelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation